A review on spatiotemporal data model for managing data movement in geographical information systems (GIS) - Mohd. Rahim, Mohd. Shafry; Mohamed Shariff, Abdul Rashid; Mansor, Shattri; Mahmud, Ahmad Rodzi (Penerbit UTM Press, 2005)
This paper reviews the development of spatiotemporal data models. Geographic data encompasses all information related to phenomena in the real world including temporal information. In this paper, we focus on the spatiotemporal data where spatial data changes over time and involves geographic movement. From our review, we found twelve classifications of geographic movement. To manage geographic movement information we require a good data model. A good data model provides for good data management. The spatiotemporal data model is a suitable to use in GIS for making easy data management of geographic data to support spatiotemporal analysis. Our review revealed nine spatiotemporal data models which can be used to manage geographic movement data or change activities in the world. Some of the models are extended from the spatial data model by including time and some are new models based on the event. Spatiotemporal data models can be use to replace current spatial data models in the GIS. We have done a comparative study with the nine models and the results of this comparison are presented in this paper.